1992
DOI: 10.1016/0009-2614(92)90055-r
|View full text |Cite
|
Sign up to set email alerts
|

Electron photodetachment from a Dirac bubble potential. A model for the fullerene negative ion CC60−

Abstract: A model for the fullerene anion C, is proposed in which the outer electron moves in an attractive deltafunction potential in the shape of a spherical bubble. Exact solutions for this "Dirac bubble potential" were previously worked out. On the basis of this model, the photodetachment cross-section and its angular distribution are computed as functions of photoelectron energy, for the electron in both S-like and P-like bound states. Secondary maxima and minima in the cross section appear at higher energy values,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 12 publications
0
30
0
Order By: Relevance
“…A monovalent C60-anion has been described by Lohr and Blinder [10]. They have assumed that a C60 molecule of Ih symmetry can be treated as an almost spherical formation and applied the Dirac bubble potential model for description of the bound and continuum electron states.…”
Section: Anions and Cations Of C6omentioning
confidence: 99%
“…A monovalent C60-anion has been described by Lohr and Blinder [10]. They have assumed that a C60 molecule of Ih symmetry can be treated as an almost spherical formation and applied the Dirac bubble potential model for description of the bound and continuum electron states.…”
Section: Anions and Cations Of C6omentioning
confidence: 99%
“…This "Dirac bubble potential" had previously been applied to model the Fermi contact interaction [ll] and the photodetachment of an electron from the Cbo molecule [12]. Our model for He2 requires just two parameters: the equilibrium separation ro and the effective strength of the potential, as represented by the constant a .…”
Section: Modelmentioning
confidence: 99%
“…
The physicochemical properties of ëé 2 solutions in the supercritical state (sc-ëé 2 ) have been extensively studied in the past decade [1][2][3][4]. This interest stems from the fact that sc-ëé 2 is an environmentally safe solvent that substitutes for toxic nonpolar solvents, such as acetone, methanol, and toluene, in industry.
…”
mentioning
confidence: 99%
“…Based on analysis of the symmetry and magic numbers of the clusters, we suggested dodecahedral and icosahedral structures of the anionic clusters and , respectively. Both clusters have spherical symmetry, which makes it possible to use the Dirac bubble model potential [4] in calculations of the electron-cluster interaction.) 13 -Analysis of the spatial structures of clusters provides rich information on the interaction of their constituent atoms and molecules and allows one to select appropriate model potentials in calculations of their properties. Shkrob and Sauer [3] suggested that the nucleus of the atomic clusters with n ≤ 6 and n ≥ 14 is the dimer, whereas, in the clusters with 6 < n < 14, the nucleus is the ion, which interacts with surrounding molecules with a binding energy of 0.22 eV per molecule.…”
mentioning
confidence: 99%
See 1 more Smart Citation